English Language Teaching Problems in Nepal: Teachers’ Perspectives (Journal of NELTA, 2024)
This paper, using the narrative inquiry method, explores English language teachers' perspectives on English Language Teaching (ELT) problems in Nepal. For this purpose, four English language instructors from four community schools located in the Rupandehi area were purposively chosen. The data were collected using semi structured interviews, and the analysis of the data was made using thematic analysis. The findings show that the mixed ability classrooms, unprepared and over-loaded teachers with low payment, poor infrastructure and resource limitations and lack of implementation of the education policy were the major challenges teachers face in ELT practices. The study implies that it can contribute to a better understanding of English teachers’ teaching problems in Nepal to minimize problems and enhance a better learning environment.